2017
DOI: 10.1016/j.rpor.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric influence of photon beam energy and number of arcs on volumetric modulated arc therapy in carcinoma cervix: A planning study

Abstract: The study showed no greater advantage of higher energy, and DA VMAT plan with 6 MV photon energy was a good choice of treatment for carcinoma cervix as it delivered a highly homogeneous and conformal plan with superior target coverage and better OAR sparing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 27 publications
0
13
0
1
Order By: Relevance
“…There was no significant impact of PTV location or PTV volume for the photon energy leading to superior plan quality. [28][29][30] Mean dose of femoral heads reduced significantly in dual arcs. It may be explained on the basis of reduced scatter dose and lesser beam-on time with rapid arc technique.…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant impact of PTV location or PTV volume for the photon energy leading to superior plan quality. [28][29][30] Mean dose of femoral heads reduced significantly in dual arcs. It may be explained on the basis of reduced scatter dose and lesser beam-on time with rapid arc technique.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the skin and NTID are not typical OARs for rectal planning, hence were not configured in the RapidPlan model. They were analyzed in this work as indicators of superficial dose and normal tissue sparing in accordance with previous studies on beam energies[4,10]. Classical radiotherapy principle recommended higher beam energy for deep seated large tumors [1], but lower energy can reduce exit dose [22] and Pirzkall et al reported negligible difference among different energies when more than 9 IMRT fields were used [5].…”
Section: Discussionmentioning
confidence: 86%
“…D x% indicates the minimum dose received by x% of the volume. In addition to conventional OARs such as urinary bladder, femoral heads and small bowel, the normal tissue integral dose (NTID) was calculated for the in-field body volume excluding PTV, and the in-field skin dose was calculated in the volume 5 mm under the body surface in accordance with previous dosiemtric studies on photon energies[4,10]. Normality test was first performed to the results of each group, followed by two-way ANOVA (repeated measures on the same individual without replication in each subgroup) and multiple paired T test (with significant level adjusted to 0.016) for further comparison if AVOVA tests reported P<0.05 (statistically significant, right-tailed).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Serviks kanseri dünyada kadınlar arasında en sık görülen 4. kanser türüdür, kanser ölümlerinin de % 7,5'ini kapsamaktadır. 1 Türkiye de ise kadın kanserlerinde dokuzuncu sıradadır. Başlıca etkeni Human Papillomavirus (HPV) olan bu kanser ülkemizde düşük sıklıkta görülmesine rağmen, Uluslararası Kanser Araştırma Ajansı tarafından yapılmış olan analizlerde HPV'ye bağlı kanserler erkek kanserlerinin %1, kadın kanserlerinin ise %5-10'undan sorumludur.…”
unclassified